Bioethical analysis of the transhumanist current and the eugenic initiative for an axiological reflection - Contreras Calderón, Joan (2024)
The first part of this article presents the modern approach to transhumanism and its respective bioethical analysis, aiming to present this analysis under a scheme of reasonableness rather than a search for accuracy after having expressed in a summarized but concise manner the premises of the intriguing eugenic movement and the positions of various authors in this regard, thus expanding the current description of the techno-scientific state of transhumanist ideas and their desperate emphasis on the improvement of disruptive and emerging biotechnologies. In a second part of the text we will approach the concept of Eugenics and its development from what we know today as Directed Evolution (DE), analyzing axiologically the necessity, the consequences and the conflicts of this concept by virtue of its understanding of the human being, proposing a vision that transcends the conception of a uniquely biological organism, criticizing mechanistic, utilitarian and reductionist aspects that transhumanism confers to its understanding of the "human being". Finally, in a third and last part, we will analyze the bioethical problems of the eugenic idea with the help of the essay "the ambush" by Ernest Jünger in order to seek an objective, axiological and metaphysical analysis to define the techno-scientific approach to the human being as an end and not as a means.